SWOT Analysis With Importance Performance Analysis (IPA) Model on QRIS Technology Service for MSMEs - Pratama, Wahyu; Latifah, Fitri Nur (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This study applies Importance-Performance Analysis (IPA) and (Strengths, Weaknesses, Opportunities, and Threats) SWOT analysis to evaluate Quick Response Code for Payment (QRIS) technology services in Micro, Small, and Medium Enterprises (MSMEs). IPA results show variables in Quadrant I (top priority for improvement), Quadrant II (maintain quality), Quadrant III (low priority), and Quadrant IV (may be excessive). In this context, data security risks and QRIS controllability were identified as top priorities. SWOT analysis, based on IPA results, reveals MSME strengths in security risk control and QRIS controllability, as well as weaknesses in variables that are considered low-priority or possibly excessive. Opportunities lie in potential improvements to data security and QRIS controllability, while threats may arise from variables that are considered low priority or may be overrated. Recommendations involve focusing on developing data security, maintaining good service quality, and efficient resource allocation according to the needs of MSMEs.